Подбор в комплект двухслойных хромоникилевых валков исполнения ЛПХНМд - Автухов, А. К. (НТУ "ХПИ", 2015)
В статье представлены основные методы, используемые при комплектовании двухслойных хромоникелевых валков перед установкой в клеть листовых станов. Приведены результаты по изучению возможности прогнозирования наработки валков. Показано, что магнитный контроль по коэрцитивной силе рабочего слоя прокатных валков при комплектовании позволяет подобрать валки с одинаковым ресурсом и повысить эффективность их использования.

In the article presents the main methods used for completing of chrome-nickel two-layer rolls before installation in the stand of sheet mills. Shown that the magnetic method is the most effective because it provides the opportunity to register inhomogeneities active layer due to technological problems in the manufacture and arising from the accumulation of stress. The results of the study on the possibility of predicting operating time of rolls, which indicate that mean indicators operating time sets of rollers, which selected on coercive force higher than selected on hardness. It is shown that the magnetic monitoring of the coercive force of the active layer of mill rolls at completing allows to select the rolls with the same resources and increase efficiency of their use.
Selection to the set of chrome-nickel two-layer rolls by LPHNMd
Keywords: валки прокатные; слой рабочий; ресурс; контроль магнитный; сила коэрцитивная; mill rolls; completing; active layer; resource; magnetic monitoring; coercive force